A Lei de Anistia e a sentença da Corte Interamericana de Direitos Humanos no caso Guerrilha do Araguaia - Souza, Lucas Monteiro de (2016)
This paper has as its purpose to analyze the Inter-American Court of Human Rights Decision in the case Guerrilha do Araguaia , specifically regarding the compatibility, or not, between the Brazilian Amnesty Law and the American Convention on Human Rights, as well as to analyze the Brazilian obligation, or not, to fulfill the terms of such Decision. Based on a theoretical landmark that attributes to human rights international treaties a special character, as jus cogens, it will be analyzed herein the main aspects of such international treaties when internalized within the Brazilian Law, as well as the general aspects of the Brazilian Amnesty Law, to conclude analyzing the specific matter of the Inter-American Court of Human Rights Decision in the case Guerrilha do Araguaia . This paper is presented through bibliographical and jurisprudence research of an exploratory-descriptive character, with the use of both inductive and deductive methods for achieving the main findings